Hydrogen-bonded trimers of DNA bases and their interaction with metal cations: ab initio quantum-chemical and empirical potential study - Sponer, J; Burda, J V; Mejzlík, P; Leszczynski, J; Hobza, P (Journal of biomolecular structure & dynamics, 1997)
Neutral (G.GC, A.AT, G.AT, T.AT, and C(imino).GC) and protonated (CH+.GC and AH+.GC) hydrogen-bonded trimers of nucleic acid bases were characterized by ab initio methods with the inclusion of electron correlation. In addition, the influence of metal cations on the third-strand binding in Purine-Purine-Pyrimidine (Pu.PuPy) reverse-Hoogsteen triplets has been studied. The ab initio calculations were compared with those from recently introduced force fields (AMBER4.1, CHARMM23, and CFF95). The three-body term in neutral trimers is mostly negligible, and the use of empirical potentials is justified. The only exception is the neutral G.GC Hoogsteen trimer with a three-body term of -4 kcal/mol. Protonated trimers are stabilized by molecular ion-molecular dipole attraction and the interaction within the complex is nonadditive, with the three-body term on the order of -3 kcal/mol. There is a significant induction interaction between the third-strand protonated base and guanine. The calculations indicate an enhancement of the third-strand binding in the G.GC reverse-Hoogsteen trimer due to-metal cation coordination to the N7/O6 position of the third-strand guanine. Interactions between metal cations and complexes of DNA bases are in general highly non-additive; the three-body term is above-10 kcal/mol in a complex of a divalent cation (Ca2+) with the GG reverse-Hoogsteen pair. The pairwise additive empirical potentials qualitatively underestimate the binding energy between cation and base.
Keywords: zastoupení bazí; Cytosine; Nucleic Acid Conformation; Guanine; Adenine; molekulární struktura; Computer Simulation; Molecular Structure; adenin; thymin; vodíková vazba; Software; kationty; molekulární modely; Cations; Models, Molecular; konformace nukleové kyseliny; kalorimetrie; Calorimetry; kovy; cytosin; Base Composition; DNA; počítačová simulace; Metals; software; Thymine; Hydrogen Bonding; guanin